Effect of Temperature and Storage Duration on the Growth of Salmonella spp. in Local Yogurt and Butter from Sulaymaniyah Markets - Dlsher Mohammed; Dawod Noori M.Shekhani (Journal of Discoveries in Applied and Natural Science, 2026)
Salmonella spp. has become one of the main foodborne pathogens at an international level, and the presence of these organisms in dairy products poses a significant human health hazard, especially in those areas where less developed methods of food processing are used and where the administrative control is not strict. This study aimed at determining how the storage temperature (4 0 C vs. 25 0 C) and the storage period (0 vs. 10 days) of commercially available yet crude yogurt and butter products distributed in Sulaymaniyah, Iraq, affected their survival and growth of Salmonella spp. Sixty dairy samples, 30 yogurt and 30 butter samples, were inoculated with well-characterised strains of Salmonella and then incubated at the predetermined point of intervals using standard microbiological techniques. Findings showed that storage at 4 o C did reduce the amount of Salmonella in both types of products significantly, and a significant rise in the amount of pathogen load was observed after storage at 25 o C, particularly in yogurt, which has greater moisture and water activity. Butter, on the other hand, exhibited significantly higher microbiological stability presumably due to reduced water activity and an increase in fat level. The results are supportive in the predictive microbiological models and the literature that exists to support the essential roles that water activity, temperature, and storage conditions have in pathogen dynamics. The research highlights the urgency behind the implementation of cold-chain logistics, improvement of packaging systems and supporting the health practice of the population on traditional dairy products to reduce the risk of microbes. To help avoid spreading salmonellosis caused by contaminated dairy products, there is a necessity to promote food safety education and strict hygienic standards when handling and disposing them.